Correlation of Attitudes towards Frequency of Fast Food Consumption in Young Adults - Citra Dewi Anggraini; Amalina Rizma; Siska Pratiwi; Herviana Herviana (Lembaga Pengembangan Kinerja Dosen, 2025)
Fast food is a type of food with a fast processing process and tends to contain high levels of sugar, salt, and fat. The effects of consumed excessive of fast food will trigger the risk of degenerative diseases. Individual attitudes will influence the amount of fast food consumption in that individual. The aim of this study was to analyzed the correlation between attitudes and the frequency of fast food consumption. The research method was observational with a cross-sectional design. The total sample in this study was 158 samples with the criteria of young adults (19-29 years) and lived in Kepulauan Riau. Collected data were attitudes and frequency of fast food consumption by filling out a questionnaire. Data analysis used was bivariate analysis with the Spearman rank statistical test. The results showed a relationship between attitudes towards fast food consumption and frequency of fast food consumption (p = 0.001) and a correlation coefficient value of -0.262. This study concluded that subjects with negative attitudes towards fast food tend to consume fast food frequently.